The tyrosine phosphatase Shp2 interacts with NPM-ALK and regulates anaplastic lymphoma cell growth and migration. - Voena, C; Conte, C; Ambrogio, C; Boeri Erba, E; Boccalatte, F; Mohammed, S; Jensen, O; Palestro, G; Inghirami, G; Chiarle, R (2007)
Anaplastic large cell lymphomas (ALCL) are mainly characterized by the reciprocal translocation t(2;5)(p23;q35) that involves the anaplastic lymphoma kinase (ALK) gene and generates the fusion protein NPM-ALK with intrinsic tyrosine kinase activity. NPM-ALK triggers several signaling cascades, leading to increased cell growth, resistance to apoptosis, and changes in morphology and migration of transformed cells. To search for new NPM-ALK interacting molecules, we developed a mass spectrometry-based proteomic approach in HEK293 cells expressing an inducible NPM-ALK and identified the tyrosine phosphatase Shp2 as a candidate substrate. We found that NPM-ALK was able to bind Shp2 in coprecipitation experiments and to induce its phosphorylation in the tyrosine residues Y542 and Y580 both in HEK293 cells and ALCL cell lines. In primary lymphomas, antibodies against the phosphorylated tyrosine Y542 of Shp2 mainly stained ALK-positive cells. In ALCL cell lines, Shp2-constitutive phosphorylation was dependent on NPM-ALK, as it significantly decreased after short hairpin RNA (shRNA)-mediated NPM-ALK knock down. In addition, only the constitutively active NPM-ALK, but not the kinase dead NPM-ALK(K210R), formed a complex with Shp2, Gab2, and growth factor receptor binding protein 2 (Grb2), where Grb2 bound to the phosphorylated Shp2 through its SH2 domain. Shp2 knock down by specific shRNA decreased the phosphorylation of extracellular signal-regulated kinase 1/2 and of the tyrosine residue Y416 in the activation loop of Src, resulting in impaired ALCL cell proliferation and growth disadvantage. Finally, migration of ALCL cells was reduced by Shp2 shRNA. These findings show a direct involvement of Shp2 in NPM-ALK lymphomagenesis, highlighting its critical role in lymphoma cell proliferation and migration.